Correlation Between the Level of Knowledge and the Stigma Toward People Living with HIV/AIDS - Amalia Salma Anindya; Kurnia, Sri Indra (Jurnal Keperawatan, 2023)
The trend of HIV/AIDS cases in Indonesia is gradually increasing with Central Java province having the highest number of cases. The lack of knowledge about HIV will trigger the emergence of stigma against PLHIV. The stigma of society makes people with HIV/AIDS become closed and isolated so that a person sees himself as useless. As well as the high stigma towards PLHIV among students, this study aims to determine the relationship between the level of knowledge and stigma towards PLHIV in students of Universitas Muhammadiyah Surakarta. The type of research used was descriptive correlation with a cross sectional approach. The sampling technique used in this study was accidental sampling with a population of all students enrolled in the class of 2019 to 2022 and a sample of 394 students was obtained. The data were then analyzed using the Spearman Rank Correlation test. The results showed that there was a relationship between the level of HIV/AIDS knowledge and stigma towards PLHIV with a p value of 0.000, the strength of the relationship was very strong (r = 0.809) and negatively patterned, meaning that the higher the level of knowledge, the lower the stigma given.